Physical Fitness and Exercise During the COVID-19 Pandemic: A Qualitative Enquiry - Kaur, Harleen; Singh, Tushar; Arya, Yogesh Kumar; Mittal, Shalini (Frontiers in Psychology, 2020)
The COVID-19 pandemic has brought this fast-moving world to a standstill. The impact of this pandemic is massive, and the only strategy to curb the rapid spread of the disease is to follow social distancing. The imposed lockdown, resulting in the closure of business activities, public places, fitness and activity centers, and overall social life, has hampered many aspects of the lives of people including routine fitness activities of fitness freaks, which has resulted in various psychological issues and serious fitness and health concerns. In the present paper, the authors aimed at understanding the unique experiences of fitness freaks during the period of lockdown due to COVID-19. The paper also intended to explore the ways in which alternate exercises and fitness activities at home helped them deal with psychological issues and physical health consequences. Semi-structured telephone interviews were conducted with 22 adults who were regularly working out in the gym before the COVID-19 pandemic but stayed at home during the nationwide lockdown. The analysis revealed that during the initial phase of lockdown, the participants had a negative situational perception and a lack of motivation for fitness exercise. They also showed psychological health concerns and overdependence on social media in spending their free time. However, there was a gradual increase in positive self-perception and motivation to overcome their dependence on gym and fitness equipment and to continue fitness exercises at home. Participants also tended to play music as a tool while working out. The regular fitness workout at home during the lockdown greatly helped them to overcome psychological issues and fitness concerns.